2023
DOI: 10.1111/cod.14287
|View full text |Cite
|
Sign up to set email alerts
|

Applying skin protective cream and the wearing of gloves?—A randomized controlled experimental study

Abstract: Background: Glove occlusion might enhance skin sensitivity to a subsequent detergent challenge (occlusion effect). Thus, some skin protection creams (PC) claim to protect against this effect of occlusion, and are recommended to be used before wearing liquid-proof gloves.Objectives: To evaluate the effect of PC applied prior to glove occlusion on the 'occlusion effect'-refers to increased susceptibility of the skin to a model detergent.Methods: One hundred and eleven volunteers were enrolled in a single-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Interestingly, PPs did not mitigate the skin’s susceptibility to the model detergent sodium dodecyl sulfate (SDS). After an irritation challenge, some even aggravated irritation compared to occlusion alone [ 7 ]. Other studies have shown that occlusion can decrease the skin’s barrier function after prolonged wear, which may cause irritation and worsening of pre-existing skin diseases [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PPs did not mitigate the skin’s susceptibility to the model detergent sodium dodecyl sulfate (SDS). After an irritation challenge, some even aggravated irritation compared to occlusion alone [ 7 ]. Other studies have shown that occlusion can decrease the skin’s barrier function after prolonged wear, which may cause irritation and worsening of pre-existing skin diseases [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%